Advances in serous tubal intraepithelial carcinoma: correlation with high grade serous carcinoma and ovarian carcinogenesis - Li, Hong-Xia (e-Century Publishing Corporation, 2014)
Early serous carcinoma in fallopian tube or serous tubal intraepithelial carcinoma (STIC), an early lesion limited to the epithelium of the fallopian tube and firstly identified from specimen obtained by prophylactic salpingo-oophorectomy, has provided insight into pelvic high grade serous carcinoma (HGSC). Increasing evidence indicates that STIC is a likely precursor for HGSC and several studies have focused on this lesion and its clinical significance. This review addresses recent advances in recognizing STIC and its correlation with HGSC and ovarian carcinogenesis. It also describes evidence regarding the fallopian tube as a source of some HGSCs, the protocol for optimizing histological evaluation of the tubes, the spectrum of tubal lesions from benign to noninvasive carcinoma, changes in diagnostic criteria from purely morphologic characteristics to a combination of morphologic features and molecular biomarkers, and new studies about potential biomarkers. However, the direct evidence regarding STIC as the precursor of HGSC is still tantalizing due to other possibilities that may also explain the origin of pelvic HGSC. Further molecular genetic studies are required to address this important question.